RISIKO PRODUKSI DAN EFISIENSI TEKNIS USAHATANI PADI PADA SAWAH TADAH HUJAN DI KABUPATEN MAROS, SULAWESI SELATAN - Arifin, Arifin; Zulkifli, Zulkifli; Biba, Muhammad Arsyad; Pata, Abdul Asis; Sadat, Mohammad Anwar (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
The The agricultural production risk is greater than non-agriculture risk because agriculture strongly affected by nature such as weather, pest, diseases, temperature, drought, and flooding. The increasing of production through technical efficiency is important to do. The technical efficiency of rice farming can be improved the support or efforts of efficient use of inputs technological innovation. The aim of this study is to analyze the risk of rice farming production in rainfed rice fields. Production risk is analyzed by determining the coefficient of variation. Production risk can be measured by the amount of variance and deviation standard. Technical efficiency is used to analyze the level of technical efficiency. The results showed that rice production risk in rainfed lowland rice in Allepolea Village was greater than the production risk in Bontoa Village and Mattirotasi Village. While for technical efficiency in Mattirotasi Village, it’s more technically efficient for rainfed lowland rice farming than in Bontoa Village and Allepolea Village, Maros Regency.